2020
DOI: 10.1080/15548627.2020.1713644
|View full text |Cite
|
Sign up to set email alerts
|

Atg38-Atg8 interaction in fission yeast establishes a positive feedback loop to promote autophagy

Abstract: Macroautophagy (autophagy) is driven by the coordinated actions of core autophagy-related (Atg) proteins. Atg8, the core Atg protein generally considered acting most downstream, has recently been shown to interact with other core Atg proteins via their Atg8-family-interacting motifs (AIMs). However, the extent, functional consequence, and evolutionary conservation of such interactions remain inadequately understood. Here, we show that, in the fission yeast Schizosaccharomyces pombe, Atg38, a subunit of the pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 75 publications
1
31
0
Order By: Relevance
“…By contrast, Atg11(522-583) rescued atg11Δ as well as full-length Atg11 ( Figure 1F ). Similar results were obtained using the Pho8Δ60 assay, where we expressed the autophagy reporter S. cerevisiae Pho8Δ60 in S. pombe pho8Δ background ( Yu et al, 2020 ; Figure 1G ). These results show that Atg11(522-583) is necessary and sufficient for the autophagy function of Atg11.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…By contrast, Atg11(522-583) rescued atg11Δ as well as full-length Atg11 ( Figure 1F ). Similar results were obtained using the Pho8Δ60 assay, where we expressed the autophagy reporter S. cerevisiae Pho8Δ60 in S. pombe pho8Δ background ( Yu et al, 2020 ; Figure 1G ). These results show that Atg11(522-583) is necessary and sufficient for the autophagy function of Atg11.…”
Section: Resultssupporting
confidence: 79%
“…Pho8∆60 activity assay was performed as described in S. cerevisiae ( Noda et al, 1995 ) with some modifications ( Yu et al, 2020 ). About 5 OD 600 units of cells were collected and washed with 0.85% NaCl, and then resuspended in 200 μL of lysis buffer (20 mM PIPES, pH 6.8, 50 mM KCl, 100 mM KOAc, 10 mM MgSO 4 , 10 μM ZnSO 4 , 0.5% Triton X-100, 2 mM PMSF) and incubated at room temperature for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the fission yeast Schizosaccharomyces pombe has become an important model organism for studying autophagy (Kohda et al, 2007;Liu et al, 2015;Mukaiyama et al, 2009Mukaiyama et al, , 2010Nanji et al, 2017;Sun et al, 2013;Suzuki et al, 2015;Yu et al, 2020;Zhao et al, 2016). In this work, we identified a previously uncharacterized S. pombe protein, Epr1, as an Atg8-interacting autophagy receptor required for ER stress-induced ER-phagy.…”
Section: Introductionmentioning
confidence: 75%
“…To test this idea, we examined whether Epr1 can be substituted by an artificial soluble tether that can interact simultaneously with both Atg8 and VAPs (Figure 4D). This tether consists of GFP, an artificial AIM (AIM art ) (Wu et al, 2015;Yu et al, 2020), and a (H) Quantification of the percentages of autophagosomes containing AuNP-labeled ER membranes observed in (G) (mean ± SD). Three independent experiments were performed.…”
Section: The Main Function Of Epr1 In Er-phagy Is To Bridge An Atg8-vap Connectionmentioning
confidence: 99%
“…Atg38 helps to maintain the integrity of the PtdIns3K complex. A previous study identified that Atg38 can also interact with Atg8 via an ATG8-interacting motif (AIM), which is responsible for the PAS accumulation of the PtdIns3K complex [ 31 ]. Sequence homologs of these genes, except ATG38, have been found in plants.…”
Section: Comparison Of Plants and Yeast Core Autophagy Componentsmentioning
confidence: 99%